Digital Marketing Sosial Media Gaming Berbayar - Kiki Sumanti; Nur Elfi Husda; Juwintar Febriani Arwan (Prosiding, 2022)
Sosial media is very effective and efficient in digital marketing in this modern era. In the world of gaming, sosial media is also functioned as an additional facility to give additional comfort and function to user. This paper is written to discuss and understand the concept of paid sosial media gaming, the right strategy to paid sosial media gaming, implantation of marketing mix to paid sosial media gaming, and marketing communication to paid sosial media gaming. The methodology used in this paper is descriptive analysis with literature research to describe the purpose of this research. The result of this study discusses about the characteristics of paid sosial media gaming, marketing strategy of paid sosial media gaming, marketing mix of paid sosial media gaming, and marketing communication for paid sosial media gaming. The result of this paper also discuesses about the design of canvas model of paid sosial media gaming and the SOSTAC of the application of the paid sosial media gaming called MaYo!! so that the business can be launched. MaYo!! is made for gamers to interact with one other as other sosial medias do which are adding friends and chatting with other gamers. Through MaYo!! players account can also be played by jockey until a certain level that customer requested and players can also pick other available MaYo pro-players to play along with to gain victory